Femmes, violences et espace public: une réflexion sur les politiques de sécurité - Lieber, Marylène (Lien social et Politiques, 2002)
Lorsqu'on se penche sur les politiques publiques concernant les violences en France, on relève une division des compétences entre les politiques dites « de sécurité » et les politiques « contre les violences faites aux femmes ». On constate que les politiques de sécurité, en se basant sur les statistiques de criminalité et de victimation, portent essentiellement sur l'espace public et marginalisent les violences faites aux femmes dans l'espace privé. Pour autant, elles ne prennent pas non plus en considération les violences perpétrées à leur encontre dans l'espace public. Or, divers exemples venant de pays étrangers esquissent des réponses faites par les pouvoirs publics à ces violences
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; cours; discipline; droits des femmes*; europe; france; histoire et politique; pol4102; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexisme; sociologie; systèmes d'oppressions; sécurité; thématiques; violences

Gender equity and socioeconomic inequality: a framework for the patterning of women's health - Moss, Nancy E (Social Science & Medicine, 2002)
This paper explores the interrelationship of gender equity and socioeconomic inequality and how they affect women's health at the macro- (country) and micro- (household and individual) levels. An integrated framework draws theoretical perspectives from both approaches and from public health. Determinants of women's health in the geopolitical environment include country-specific history and geography, policies and services, legal rights, organizations and institutions, and structures that shape gender and economic inequality. Culture, norms and sanctions at the country and community level, and sociodemographic characteristics at the individual level, influence women's productive and reproductive roles in the household and workplace. Social capital, roles, psychosocial stresses and resources, health services, and behaviors mediate social, economic and cultural effects on health outcomes. Inequality between and within households contributes to the patterning of women's health. Within the framework, relationships may vary depending upon women's lifestage and cohort experience. Examples of other relevant theoretical frameworks are discussed. The conclusion suggests strategies to improve data, influence policy, and extend research to better understand the effect of gender and socioeconomic inequality on women's health.
Keywords: approches et analyses; projet charge mentale; ressource en ligne; santé; santé des femmes*; sexisme; stéréotypes de genre; systèmes d'oppressions; thématiques; violences; violences économiques